An international review of the use of competency standards in undergraduate pharmacy education - Nash, R.; Stafford, Leanne; Brown, N.; Jackson, S.; Peterson, G. (International Pharmaceutical Federation, 2015)
© 2015 FIP.Background: Pharmacists are self-regulating health professionals. There is currently international attention on pharmacy education, competency standards, advanced level frameworks and integrated pharmacy programmes. Aims: To review the programme-wide use of competency standards within undergraduate pharmacy curricula internationally. Methods: A systematic review of the literature was undertaken between 2000-2013. An iterative process using constant comparative analysis was utilised to theme the final 19 papers. These papers were then characterised based on their programme level use of competency standards. Results: Of 948 articles identified, 19 were included. Competency standards were used multiple ways in pharmacy programmes including curriculum design, mapping and were reflected in assessment. Conclusion: Across the globe the profession’s competency standards (CS) have been utilised to design, develop and review pharmacy curricular. Use of CS to inform outcome-based education (OBE) in pharmacy programmes provides a quality assurance mechanism and may enhance the accountability and flexibility of the profession for its public.